2019
DOI: 10.1111/psyp.13456
|View full text |Cite
|
Sign up to set email alerts
|

When the outcome is different than expected: Subjective expectancy shapes reward prediction error at the FRN level

Abstract: Converging evidence in human electrophysiology suggests that evaluative feedback provided during performance monitoring (PM) elicits two distinctive and successive ERP components: the feedback‐related negativity (FRN) and the P3b. Whereas the FRN has previously been linked to reward prediction error (RPE), the P3b has been conceived as reflecting motivational or attentional processes following the early processing of the RPE, including action value updating. However, it remains unclear whether these two consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
(174 reference statements)
4
6
0
Order By: Relevance
“…In conclusion, the results of this study add to the current body of literature in discussing the underlying generators of the RewP by directly comparing effects of reward and timing uncertainty on RewP amplitude. The current results confirm that uncertain trials elicit greater RewP amplitude, when compared to certain trials (Hajcak et al, 2007;Pfabigan et al, 2011;Walentowska et al, 2019;Xu et al, 2011), which supports theoretical arguments that the RewP indexes a reward prediction error. These results also add, however, that this effect is driven by uncertainty specifically surrounding the reward and is unchanged by uncertainty surrounding the timing of feedback presentation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In conclusion, the results of this study add to the current body of literature in discussing the underlying generators of the RewP by directly comparing effects of reward and timing uncertainty on RewP amplitude. The current results confirm that uncertain trials elicit greater RewP amplitude, when compared to certain trials (Hajcak et al, 2007;Pfabigan et al, 2011;Walentowska et al, 2019;Xu et al, 2011), which supports theoretical arguments that the RewP indexes a reward prediction error. These results also add, however, that this effect is driven by uncertainty specifically surrounding the reward and is unchanged by uncertainty surrounding the timing of feedback presentation.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the current study provides evidence for increased motivational salience of rewards compared to the timing of reward or non-reward presentation (cf., Pegg & Kujawa, 2020). As expected, we found that larger RewP amplitudes were present on uncertain reward trials compared to certain reward trials, confirming previous studies that have shown the same or similar effect (Hajcak et al, 2007;Pfabigan et al, 2011;Walentowska et al, 2019). However, contrary to our hypothesis, RewP amplitude did not significantly differ between certain and uncertain trials on the timing cued task where participants were cued to the timing of reward presentation but not the presence/absence of reward.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings in the current study do not provide supportive evidence for the negative outcome bias reflected by FRN (e.g., loss outcomes always elicit a more negative FRN). Instead, it supports evidence showing that the FRN reflects the degree of unexpectedness irrespective of valence (i.e., better‐ or worse‐than‐expected outcomes; Ferdinand et al., 2012; Walentowska et al., 2019). Future studies will have to explore the reason why FRN only respond to expectation violation rather than outcome valence or the interaction of outcome valence and expectation violation in the Chicken game task involving monetary reward.…”
Section: Discussionsupporting
confidence: 74%
“…Proudfit (2015) proposed that the fERN, MFN, and FRN are reward positivity (RewP), which provides an appropriate description of the scalp‐recorded difference between the ERP elicited by the gain (correct) and loss (incorrect) feedback. Besides an index of differentiating the valence of feedback, the feedback‐locked ERP component, especially FRN, also can be regarded as an “expectation violation” signal that codes for expectation independent of valence (Ferdinand et al., 2012; Walentowska et al., 2019). The violation of expectations leads to a more negative‐going FRN deflection (Gu et al., 2020; Pfabigan & Alexopoulos, 2011; Van der Molen et al., 2013).…”
Section: Introductionmentioning
confidence: 99%